2004
DOI: 10.1111/j.1751-1097.2004.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Photodynamic Properties of 13, 15‐N‐cycloimide Derivatives of chlorin p6

Abstract: Comparative study of 13,15‐[N‐(2‐hydroxyethyl)]cycloimide chlorin p6 (2), 13,15‐(N‐acetoxy)cycloimide chlorin p6 (3), 13,15‐(N‐hydroxy)cycloimide chlorin p6 methyl ester (4) and 13,15‐(N‐methoxy)cycloimide chlorin p6 methyl ester (5) together with the previously investigated 13,15‐[N‐(3‐hydroxypropyl)]cycloimide chlorin p6 (1) was performed. The dependence of the key photodynamic properties of 1–5 on the introduced substituents was analyzed. The photoinduced cell‐killing activity of 4 is 100‐ and 280‐fold high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition, they were similar to the spectra recorded from these compounds in solution with 1% CrEL (Figure , III). Previous studies showed that CrEL emulsion was well suited to model cellular lipid-like environment of hydrophobic chlorine and bacteriochlorine PSs. ,, Thus, intracellular spectral characteristics of compounds 4 and 6 are consistent with their localization in lipid structures, e.g., lipid droplets and membrane-bound organelles.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, they were similar to the spectra recorded from these compounds in solution with 1% CrEL (Figure , III). Previous studies showed that CrEL emulsion was well suited to model cellular lipid-like environment of hydrophobic chlorine and bacteriochlorine PSs. ,, Thus, intracellular spectral characteristics of compounds 4 and 6 are consistent with their localization in lipid structures, e.g., lipid droplets and membrane-bound organelles.…”
Section: Resultsmentioning
confidence: 64%
“…Lipid droplets are lipid storage and metabolic organelles . Intracellular accumulation in lipid droplets is a property of chlorine and bacteriochlorine PSs with increased hydrophobicity. , As was shown previously, cancers cells were highly sensitive (both in vitro , and in vivo) to photodynamic action initiated by PSs localized in lipid droplets.…”
Section: Resultsmentioning
confidence: 68%
“…The CSI technique was successfully used in the studies of sulfonated phthalocyanines [9][10][11], cycloimide derivatives of chlorin p 6 (CIC) [12][13][14][15][16][17][18] and bacteriochlorin p (CIBC) [19]. It helped to clarify the fact that chelating with a metal atom was not essential for the efficiency of phthalocyanines in anticancer PDT [9].…”
Section: B Study Of Photosensitizersmentioning
confidence: 99%
“…These photosensitizers absorb in the 705-745 nm range, where human tissues are relatively transparent for the exciting light. Varying different substituents the CIC derivatives were found, which accumulated intensely (distribution ratio of 5-11) in cytoplasm of cancer cells in a lipid-bound monomeric photoactive form [12][13][14][15][16]. Hydrophobic substituents provided predominant accumulation of CICD in lipid droplets.…”
Section: B Study Of Photosensitizersmentioning
confidence: 99%